2008
DOI: 10.1159/000163097
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and Risk of Sporadic Creutzfeldt-Jakob Disease in Denmark and Sweden: Registry-Based Case-Control Studies

Abstract: Background: Epidemiologic evidence of surgical transmission of sporadic Creutzfeldt-Jakob disease (sCJD) remains controversial. Methods: From Danish and Swedish registries we selected 167 definite and probable sCJD cases (with onset between 1987 and 2003) and 3,059 controls (835 age-, sex-, and residence-matched, and 2,224 unmatched). Independent of case/control status, surgical histories were obtained from National Hospital Discharge Registries. Surgical procedures were categorized by body system group and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(122 citation statements)
references
References 65 publications
3
118
1
Order By: Relevance
“…In order to improve completeness, 5 research reports, 3 of which were published before 1990, and 2 recent papers on BT and surgical history were added [13,14,15,16,17]. Thirty-three documents pertaining to case-control studies and several studied cohorts [4,5,6,7,8,9,10,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38] were examined in full text. Thirteen were excluded from the systematic review since: (a) they focused on biographic residential space-time relationships [19]; (b) they were methodological [6,7,8,20]; (c) they focused on the follow-up of national single cohorts of persons exposed to treatment with human pituitary growth hormones in the UK, The Netherlands and the USA [18,21,22,23,24], or with BT or plasma products without data on nonexposed persons [37,38], or (d) they related to human dura mater graft recipients [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve completeness, 5 research reports, 3 of which were published before 1990, and 2 recent papers on BT and surgical history were added [13,14,15,16,17]. Thirty-three documents pertaining to case-control studies and several studied cohorts [4,5,6,7,8,9,10,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38] were examined in full text. Thirteen were excluded from the systematic review since: (a) they focused on biographic residential space-time relationships [19]; (b) they were methodological [6,7,8,20]; (c) they focused on the follow-up of national single cohorts of persons exposed to treatment with human pituitary growth hormones in the UK, The Netherlands and the USA [18,21,22,23,24], or with BT or plasma products without data on nonexposed persons [37,38], or (d) they related to human dura mater graft recipients [25].…”
Section: Methodsmentioning
confidence: 99%
“…Studies on medical procedures as a risk factor for sCJD are compromised by methodological limitations [6,7]. Results of recent studies on surgical history introducing methodological improvements such as latency analysis, etiological classification of surgical procedures (SP) and SP data obtained from national registries (and, therefore, theoretically independent from recall bias) [8,9,10], have raised new hypotheses, although space-time relationships between procedures have not been observed [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic transmission of classical (sporadic) CJD by a contaminated neurosurgical instrument has been reported (5), and epidemiological evidence suggests a fraction of apparently sporadic CJD may be caused by unrecognized iatrogenic infection during general surgery (6,7). The unknown, but potentially substantial (8), prevalence of clinically silent infection with vCJD prions in populations exposed to dietary BSE prions, together with the much wider tissue distribution of infectivity in vCJD (9)(10)(11), highlights the concerns of risk of infection through contact with surgical instruments.…”
mentioning
confidence: 99%
“…Although the Centers for Disease Control and Prevention estimate that fewer than 1% of cases of sporadic CJD can be attributed to contaminated surgical instruments, 3 a recent population-based study suggests that the percentage may be as high as 18%. 4 Of note, the literature suggests that the development of symptoms may be significantly more rapid after iatrogenic transmission than would be expected in sporadic cases.…”
Section: Ethical Analysis Of Communicating the Risk Of Iatrogenic Crementioning
confidence: 99%
“…The committee's best estimate suggested that, on the basis of the paucity of documented cases of transmission of CJD during surgery, the quantitative risk of transmission of CJD was exceedingly low; however, the study by Mahillo-Fernandez et al 4 suggesting that 1 in 5 CJD cases may be attributable to surgical intervention had not yet been published. The risk of iatrogenic transmission of CJD should be considered both in the context of spontaneous incidence of CJD (approximately 1 in 1,000,000 persons) and in the context of the significantly greater risk of other serious nosocomial events (eg, the development of antibiotic-resistant infections) not routinely highlighted on hospital admission.…”
Section: Ethical Analysis Of Communicating the Risk Of Iatrogenic Crementioning
confidence: 99%